Analisis Jalur Determinan Sindrome Premenstruasi pada Remaja Putri - Destinady Kadiser Miden; Irene Febriani; Itma Annah (Poltekkes Kemenkes Kupang, 2022)
Background: Premenstrual Syndrome (PMS) is the most common health problem reported by women of reproductive age. The incidence of PMS is caused by several factors, such as stress factors, diet, sleep patterns, physical activity, and body mass index (BMI). This study aims to analyze the pattern of variable relationships that directly affect or indirectly affect a set of independent variables (exogenous) to the dependent variable (endogenous). Methods: This study was a quantitative survey of high school girls in Palangka Raya City. The sampling technique used is clustered random sampling followed by stratified random sampling. Results: Some variables had a significant direct effect on the incidence of PMS, including BMI, stress, diet, and physical activity. In addition, some variables indirectly affect the incidence of PMS through BMI variables, namely stress and physical activity. Conclusion: There is a significant relationship between both direct and indirect effects of exogenous variables on endogenous variables. It is hoped that the results of this study can reduce the incidence of PMS in adolescents both in the education and health sectors.